Penetrating Neck Injury due to Foreign Body at C5 Level with Plexus Brachialis Nerve Injury: A Case Report - Maximillian C. Oley; Eko Prasetyo; Ferdinan Tjungkagi; Yovanka N. Manuhutu; Diornald J. Mogi (Universitas Sam Ratulangi, 2022)
Abstract: Penetrating neck injury caused by screwdriver is a very rare case. Rapid transport to a major trauma center is needed for such patients to prevent neurological dysfunction and post traumatic tissue damage. Early and complete assessment and exact surgical procedure are very important to overcome a good outcome and prognosis. We reported a case of a 28-year-old male transferred to the emergency room after being stabbed using a screwdriver. No history of nausea, vomiting, and loss of consciousness. A screwdriver got stucked on the neck at the level of C5-C6 associated with edema but no active bleeding. The upper extremity examination revealed that the muscle contraction was 5555/4444, thumb test +/, opposition test +/-, abductor adductor test +/-, and sensory within normal limit. Radiology examination showed a metallic density of the foreign body in the cervical region penetrating from soft tissue to the vertebral body of cervical C5. The patient was diagnosed with penetrating neck injury due to foreign body in the posterior neck region at C5 level with plexus brachialis nerve injury. Foreign body removal and laminectomy were done to decompression purpose. This case need early, complete and adequate management to prevent post traumatic tissue damage, other neurological dysfunction, and mortality. On the fourth post-surgical day, the patient was discharged with stable vital signs and no neurological deficit. The regular follow up at the neurosurgical clinic showed that neither motoric nor sensoric deficit was found. In conclusion, penetrating neck injury which can cause severe morbidity and permanent disability need an adequate management to prevent any spinal cord damage and minimize any neurological dysfunction. Keywords: penetrating neck injury; spinal cord injury